Strategic and Financial Evaluation of New-Generation Jet Engine Maintenance Development: A Case Study on Investment Decision-Making for PT GG Aircraft Maintenance - Ari Wibowo; Oktofa Yudha Sudrajad (Publikasi Indonesia, 2026)
In the next decade, the Maintenance, Repair, and Overhaul (MRO) market is expected to undergo significant changes driven by evolving demand for aircraft and engine maintenance services. The currently dominant CFM56 engine family is gradually being replaced by the LEAP engine family, which represents a new generation of commercial aircraft engines. As one of the largest MRO providers in Southeast Asia, PT GG Aircraft Maintenance has established capabilities in CFM56 engine maintenance but faces a strategic challenge regarding whether to invest in developing LEAP engine maintenance capabilities, which requires an estimated capital expenditure of approximately USD 75 million. This investment decision is critical to ensuring the company’s long-term sustainability, particularly in maintaining competitive aircraft engine maintenance service capabilities. This study examines strategic alternatives for the company, including the development of LEAP engine maintenance capabilities through internal investment and resources, as well as the evaluation of potential collaboration schemes with investors or strategic partners, such as joint operations (JO) or joint ventures (JV) with original equipment manufacturers (OEMs) or other MRO providers. This study aims to provide strategic recommendations supported by comprehensive financial evaluations, serving as a reference for strategic decision-making to strengthen the company’s long-term competitiveness in the regional and global MRO industry.